Restoration of a small, shallow, eutrophic lake by submerged aeration and comparison with a similar lake - Zhang, Xiaoju, author; Roesner, Larry, advisor; Sharvelle, Sybil, committee member; Carlson, Kenneth, committee member; Catton, Kimberly, committee member; Stednick, John, committee member (Colorado State University. Libraries, 2013)
A submerged aeration system was introduced to Fossil Creek Lake, a small scale, shallow, eutrophic, very hard water lake, to increase hypolimnetic dissolved oxygen levels, prevent thermal stratification and improve water quality. There has been a long-standing concentration of research effort on aeration systems in deep water lakes, but very little attention has been paid to urban shallow lakes. This research describes the investigation of physical, chemical and biological parameters of the lake before and after aeration. The aeration system gradually and permanently improved the water quality of the entire lake and eliminated many undesirable lake conditions. With the destratification caused by the aeration system, the bottom water dissolved oxygen concentrations increased significantly (p<0.05) from less than 1 mg L-1 to above 4 mg L-1. Furthermore, the vertical variations of many water quality parameters have been significantly reduced with the complete mixing of the entire lake, which are: pH, specific conductance, nutrients, chlorophyll a, alkalinity, total suspended solids, sulfate, and hardness. However, limiting nutrient, trophic status and water clarity of the lake were barely affected by the aeration system. Multiple years of continuous aeration on this lake may be necessary to achieve a lower trophic condition. In addition, this research also discusses sources of extremely high sulfate and sulfide levels of Fossil Creek Lake and provides aeration startup recommendations for lakes with high sulfide concentrations. In this study, the water quality parameters, trophic status and nutrient mass balance of Fossil Creek Lake were compared with Sheldon Lake from April to December in 2010 and 2011, a turbid, phytoplankton-dominated lake, which is restored by submerged aeration after bottom sediment removal. Monthly mean values of temperature and dissolved oxygen, as well as monthly mean total alkalinity, total inorganic carbon, total organic carbon, orthophosphate and total nitrogen concentrations showed similar distributions in the two lakes. However, the total suspended solids and chlorophyll a concentrations were significantly (p<0.05) higher in Sheldon Lake than those in Fossil Creek Lake. In addition, the Secchi disk transparency of Sheldon Lake rarely exceeded 0.5 m, which was lower than Fossil Creek Lake (>1m). Models relating water clarity to monitored water quality parameters over a period of 2 years are developed in both lakes. In Fossil Creek Lake, the water clarity is not only significantly related with inorganic carbon, nitrogen and orthophosphate, but also hardness, alkalinity, total suspended solids and chlorophyll a concentrations. But in Sheldon Lake, the lake clarity is only significantly related to two parameters, which are total suspended solids and chlorophyll a concentrations.
Keywords: hydrogen sulfide; submerged aeration; nutrient balance; eutrophic; lake restoration; water quality